Understanding the concept of ecological sin - Wyrostkiewicz, Michał (Bogoslovni vestnik, 2025)
Concern for the natural environment has been an important topic in today’s world. In this context, the concept of ecological sin appears. Although it is making an increasing career in public discourse, is still ambiguous. This situation significantly distorts public and academic discussions about ecology, environmental ethics and the Anthropocene. An in-depth explanation of the issues of ecological sin and its theological and social context is the goal of this study. Since the idea of ecological sin originates from Christian theology, its full understanding requires looking at this issue from this perspective. Here, sin is presented as the misappropriation of the order discovered by reason and confirmed by experience. This article is intended to be the voice of a Christian (Catholic) moral theologian in the discourse on the Anthropocene and environmental ethics.
Keywords: anthropocene; antropocen; ecological debate; ecological morality; ecological sin; ekološka morala; ekološka razprava; ekološki greh; environmental ethics; greh; okoljska etika; sin